2019 27th European Signal Processing Conference (EUSIPCO) 2019
DOI: 10.23919/eusipco.2019.8903090
|View full text |Cite
|
Sign up to set email alerts
|

Single Image Ear Recognition Using Wavelet-Based Multi-Band PCA

Abstract: Principal Component Analysis (PCA) has been successfully used for many applications, including ear recognition. This paper presents a 2D Wavelet based Multi-Band PCA (2D-WMBPCA) method, inspired by PCA based techniques for multispectral and hyperspectral images, which have shown a significantly higher performance to that of standard PCA. The proposed method performs 2D non-decimated wavelet transform on the input image dividing the image into its subbands. It then splits each resulting subband into a number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Zarachoff et al [16] presented a two-dimensional wavelet relying on multi-band PCA (2DWMBPCA) technique, inspired through PCA based on technical for hyperspectral and multispectral images, which showed significantly higher performance than standard PCA. The suggested technique performs a non-destructive twodimensional wavelet transformation on the input image to split the image into its sub-bands.…”
Section: Introductionmentioning
confidence: 99%
“…Zarachoff et al [16] presented a two-dimensional wavelet relying on multi-band PCA (2DWMBPCA) technique, inspired through PCA based on technical for hyperspectral and multispectral images, which showed significantly higher performance than standard PCA. The suggested technique performs a non-destructive twodimensional wavelet transformation on the input image to split the image into its sub-bands.…”
Section: Introductionmentioning
confidence: 99%
“…To the authors' knowledge, no similar techniques that utilize wavelets have been reported in the literature. This has inspired the authors to propose a single image, PCA based method for ear recognition, called 2D Wavelet based Multi-Band PCA (2D-WMBPCA), which was originally introduced in EUSIPCO in [17]. Unlike the aforementioned PCA based methods, the proposed technique does not require the images to be projected into a common eigenspace.…”
Section: Introductionmentioning
confidence: 99%